(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigated the efficacy of medicinal correction strategies in mitigating cardiovascular complications induced by anthracycline therapy in patients diagnosed with acute leukemias. A retrospective cohort of 150 adult patients, treated with anthracycline-based chemotherapy between January 2015 and December 2025, who subsequently developed cardiac dysfunction (LVEF <50%, heart failure symptoms), was analyzed. Patients received guideline-directed medical therapies, primarily ACE inhibitors/ARBs and beta-blockers. The primary outcome, defined as improvement in LVEF by ≥10% or normalization to ≥50% at 12 months, was achieved by 68% of the cohort. Patients receiving ACE inhibitors/ARBs demonstrated a mean LVEF increase of 11.5%, significantly greater than the 9.8% observed in the beta-blocker group. Significant reductions in NT-proBNP levels () and improvements in NYHA functional class were also observed across the cohort, with 70% of patients improving from class III/IV to I/II. The incidence of major adverse cardiovascular events at 12 months was 18%, with adverse drug reactions occurring in 35% of patients, mostly mild and manageable. These findings suggest that timely medicinal intervention, particularly with ACE inhibitors/ARBs, can effectively improve cardiac function and clinical outcomes in patients with anthracycline-induced cardiotoxicity following acute leukemia treatment.